Pengaruh Struktur Modal, Tingkat Suku Bunga dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Thomas Firdaus Hutahaean; Elfanito Kristian Bu’ulolo (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
This study aims to examine the effect of Capital Structure, Company Size, Partially and simultaneously on Dividend Policy on Corporate Value in Property & Real Estate Companies listed on Indonesia Stock Exchange. This study used some theories relating to financial management and accounting theories related to Capital Structure, Company Size, Dividend Policy. This research used a quantitative approach, this type of research was descriptive, the nature of this research was explanatory, while the data of this study were drawn using documentation technique and the type of data used in this study was secondary data. Data analysis used in this research was doubled linear regression. The population of this study were 32 companies while the sample of this study were 128 companies. The classical assumption test used was normality test, multicollinearity test, autocorrelation test, heteroscedasticity test. The result of the coefficient of determination test shows that the effect of capital structure, interest rate, firm size is 80.9% while the remaining 19.1% were affected by other variables not examined in this research such as profitability, dividend policy , investment decisions and sales growth. The results of this study indicate that simultaneously, capital structure, interest rate, firm size had an effect on firm value. Partially, the research shows that capital structure has no effect on firm value, interest rate has no effect on firm value and firm size has a negative effect on the value of company.